Enhancing Midwifes’ Competence in Cardiopulmonary Resuscitation (Cpr) for Pregnant and Postpartum Women to Reduce Maternal Mortality Rates - Lesmana, Hendy; Budiman; Sinabutar, Nerli Adria; Hasriana; Zulfia, Rahmatuz (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
The maternal mortality rate is an indicator of women's welfare and is one of the main indicators of a country's health status. Apart from that, the maternal mortality rate indicates the quality and capacity of health services in a region. In Indonesia, the maternal mortality rate is the second highest in ASEAN. To reduce the maternal mortality rate, the role of midwives who work in health services is vital. The aim of this service is to improve the skills of midwives in carrying out cardiopulmonary resuscitation, especially for pregnant and postpartum mothers in Tana Tidung Regency. This cardiopulmonary resuscitation training activity was carried out in Tana Tidung Regency in collaboration with the Tana Tidung Regency Health Service. The training participants were 25 midwives who worked in government health service facilities. The training method is carried out by lectures and simulations of skills in carrying out cardiopulmonary resuscitation for pregnant and postpartum women, which ends with an evaluation of the participants' knowledge and skills. The results of this service activity were that there was an increase in the training participants' knowledge to good by 80% and sufficient by 20%, as well as their skills in performing cardiopulmonary resistance with a score above 80.